Efficacy on gait and posture control after botulinum toxin A injection for lower-limb spasticity treatment after stroke: A randomized controlled trial - Yu, Hui-xian; Liu, Si-hao; Wang, Zhao-xia; Liu, Chang-bin; Dai, Pei; Zang, Da-wei (Frontiers in Neuroscience, 2023)
Objectives: To observe the efficacy of botulinum toxin type A(BoNT-A) for the spasticity of the lower-limb post-stroke on gait and posture control. Methods: A total of 46 patients with hemiplegia gait were randomly divided into the experimental group (23 patients) and the control group (23 patients). In patients in the experimental group received injections of BoNT-A by electrical stimulation-guided. At the same time, patients of the two groups received routine physical therapy. Gait analysis, plantar pressure analysis, lower-limb Fugl-Meyer Assessment (L-FMA), 10MWT, timed “Up and Go” test (TUGT), and modified Ashworth scale assess (MAS) of the lower limbs were performed at 0, 1, 4, and 12 weeks after treatment. Results: At 1, 4, and 12 weeks after treatment, tne L-FMA, stride length, speed, and TUGT significantly improved than 0 week in both groups. The L-FMA and peak of forefoot pressure, and MAS results in the experimental group were better than those in the control group at 4, and 12 weeks. The TUGT, speed, and stride length in experimental group was significantly shortened than that in control group at 1, 4, and 12 weeks. Conclusion: BoNT-A injection can improve motor functions of the lower limb, gait, spasticity, forefoot pressure, and posture control of patients after stroke.